Consumer behavior aspects of snowboarding in Greece: an examination of participants’ motives, constraints andattachment to the skiing resort - Kaimakamis, Dimitrios; Mitatou, O.; Mpalaska, P. (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The present study aimed to examine snowboarders’ motives, constraints and place attachment levels with reference to their chosen skiing resort. Furthermore, the study aimed to check whether place attachment can predict snowboarders’ intention to continue participating in the activity. Material and Methods. The study sample consisted of two hundred and eighty snowboarders (n = 280). The leisure constraints and place attachment questionnaires were used. Results. The results of the study indicated that the feeling of excitement, fun and enjoyment were the most important motives, while the financial dimension had the highest mean score on the scale of constraints followed by the facilities/services (4.9) dimension. In terms of the “place attachment” construct, the place dependence factor had the highest mean score. Finally, the place dependence dimension offered the most significant contribution to the prediction of behavioral intentions (t = 5.09, p < 0.001), followed by place identity (t = 2.32, p < 0.05). Conclusions. The theoretical and applied implications of these results are discussed.
Keywords: snowboard; motives; constraints; place attachment; behavioral intentions